A first taste of Vanilla - Dobson, Simon (Trinity College Dublin, Department of Computer Science, 1998)
We present an overview of Vanilla, a system for building interpreters from components implementing language fragments. We describe Vanilla?s architecture and capabilities, and illustrate its use by defining a simple language feature.
Keywords: Computer Science